Non-Fungible Token (NFTs) Copyrights Towards Indonesia Digital Economy Development 2030 : Polemic and Challenges - Ninne Zahara Silviani; Seela Anwar Sya'adah (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2023)
In the last two decades, art and technology are increasingly inseparable. Existing technology has developed rapidly, in this case the internet which has given birth to a new era known as the digital era which was followed by the emergence of many legal problems, one of which was copyright infringement. The emergence of Non-Fungible Tokens (NFTs) is said to be able to democratize the arts industry and Indonesia digital economy decentralized. Indonesia has a regulation named the Law of the Republic of Indonesia Number 28 of 2014 which regulates the exclusive rights of creators from the industrial sector to works of art. With the existence of These Non-Fungible Tokens (NFTs) the copyright of a digital artwork is questionable. The unique thing with the existence of this Non-Fungible Tokens (NFTs) is that Non-Fungible Tokens (NFTs) does not have the same values, each unique asset cannot be exchanged, so the artists use Non-Fungible Tokens (NFTs) as a certificate of ownership of a rare digital asset. However, because there is no specific regulation regarding Non-Fungible Tokens (NFTs) either in copyright regulations or its protection by the government, there have been cases of copyright infringement intentionally or unintentionally. This research aims to analyze how Indonesian government set the pace to protect copyrights of digital artworks as a preparation for the Indonesia 2030 Digital Economy Development.